Approaches to develop marine fishing tourism in a Norway and Chinese regions. Marine fishing tourism competitiveness comparison between North Cape and Wenzhou - Zhuo, Xuejia (The University of Bergen, 2012)
Approaches to develop marine fishing tourism in a Norway and Chinese regions GEO350 MASV-GEOG